Design Build a Spider Robot Detector Fire Arduino based - Furqon, M. Hafizul; Wahyu Ciptadi, Prahenusa; Hardyanto, R. Hafid; Pratisto, Eko Harry (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2022)
Fire is an event that is not desired by every human being. Fires can cause significant losses, both material and life losses. Every fire process always causes a fire in a place or room where a fire occurs. A fire that is still not too big can be detected using a robot. Detection of the source of the fire in the kitchen room is still difficult because it is not yet known by the occupants of the house who are in another room or outside the house. Residents of the house have difficulty finding hotspots that are still small, so a robot is needed that can detect the presence of these hotspots. One of the robots that can be applied in this situation is the spider robot. This study aims to implement fire sensor technology to detect fire using Arduino. Methods of data collection using literature study and observation. The application development phase includes analysis, system design, implementation, and testing. This program is implemented using ultrasonic sensors, wi-fi modules, servos, and fire sensors. Ultrasonic sensors as a protection system from robots and IR flame sensors as sensors to detect fire. The spider robot can detect fire and provide warnings through sound alarms and can provide notifications via messages in the WhatsApp application. The fire detection robot made can detect a fire by notifying WhatsApp messages and alarms when the robot detects fire. The test results show the tool can run well. This can be proven by the value of the test results that have been carried out